Serum Periostin Level Reflects Progression of Ossification of the Posterior Longitudinal Ligament. Issue 1 (January 2022) - Kawaguchi, Yoshiharu; Kitajima, Isao; Yasuda, Taketoshi; Seki, Shoji; Suzuki, Kayo; Makino, Hiroto; Ujihara, Yasuhiro; Ueno, Tomohiro; Canh Tung, Nguyen Tran; Yahara, Yasuhito
Abstract : Background: Ossification of the posterior longitudinal ligament (OPLL), characterized by ectopic new bone formation in the spinal ligament, causes neurological impairment due to narrowing of the spinal canal. However, the etiology has not been fully elucidated yet. Several biomarkers may be related to the pathogenesis of OPLL. The present study focused on the serum level of periostin, which is recognized as an important bone formation regulator. Methods: This study included 92 patients with OPLL and 54 control patients without OPLL. For the case-control analysis, 54 age and sex-matched patients were randomly included in the OPLL group. The serum fibroblast growth factor-23 (FGF-23), creatinine, inorganic phosphate, calcium, alkaline phosphatase, and periostin levels were assessed. Furthermore, the calcium, creatinine, and inorganic phosphate levels in urine and the percentage of tubular reabsorption of phosphate were also analyzed. Moreover, the relationship between the biomarkers and the extent of OPLL was analyzed. The data were compared between patients with OPLL progression (the progression group) and without OPLL progression (the non-progression group). Results: The mean serum FGF-23 and periostin levels in the OPLL group were higher than that in the control group. The serum inorganic phosphate level in the OPLL group was lower than that in the control group. No correlation was found between any of the biomarkers and the extent of ossification. The serum periostin level in the progression group was higher than that in the non-progression group. No significant difference in the serum FGF-23 level was noted between the progression and non-progression groups. Moreover, no correlation was found between serum periostin and FGF-23 levels. Conclusions: The serum periostin level is related to OPLL progression. Level of Evidence: Prognostic Level III . See Instructions for Authors for a complete description of levels of evidence.